Analysis of Inflammatory Signaling in Human Middle Ear Cell Culture Models of Pediatric Otitis Media. (20th May 2020) - Espahbodi, Mana; Samuels, Tina L.; McCormick, Caroline; Khampang, Pawjai; Yan, Ke; Marshall, Samuel; McCormick, Michael E.; Chun, Robert H.; Harvey, Steven A.; Friedland, David R.; Johnston, Nikki; Kerschner, Joseph E.
Abstract : Objectives/Hypothesis: Cell culture models are valuable tools for investigation of the molecular pathogenesis of diseases including otitis media (OM). Previous study indicates that age‐, sex‐, and race‐associated differences in molecular signaling may impact disease pathophysiology. Currently, a singular immortalized middle ear epithelial (MEE) cell line exists, HMEEC‐1, derived from an adult without known middle ear disease. In this study, HMEEC‐1 and primary MEE cultures from pediatric patients with and without OM were stimulated with inflammatory cytokines or OM‐pathogenic bacterial lysates to examine differences in the response of molecules associated with OM pathogenesis. Study Design: Case–control series. Methods: MEE cultures were established from patients aged <6 years: two with recurrent OM (ROM), two with OM with effusion (OME), and one patient without OM who was undergoing cochlear implant surgery control undergoing cochlear implantation (Peds CI). Primary MEE cultures and HMEEC‐1 cells were stimulated with tumor necrosis factor‐α, interleukin (IL)‐1β, or nontypeable Haemophilus influenzae lysate. TNFA, IL1B, IL6, IL8, IL10, and MUC5B were assayed via quantitative polymerase chain reaction. IL‐8 was assayed by enzyme‐linked immunosorbent assay. Results: Gene/protein target expressions were frequently higher in pediatric OM lines than in HMEEC‐1 and Peds CI. HMEEC‐1 cells were frequently less responsive to stimuli than all pediatric lines. OME lines were often more responsive than ROM lines. Conclusions: OM may be associated with specific molecular phenotypes that are retained in primary cell culture. Adult‐derived HMEEC‐1 cells differ significantly in baseline expression and response of OM‐associated molecules relative to pediatric MEE cells. Work is underway to immortalize pediatric OM MEE cultures as improved tools for the OM research community. Level of Evidence: 4 Laryngoscope, 131:410–416, 2021